INFLATION EXPECTATIONS AND BEHAVIOR: DO SURVEY RESPONDENTS ACT ON THEIR BELIEFS?. (May 2015) - Armantier, Olivier; Bruine de Bruin, Wändi; Topa, Giorgio; van der Klaauw, Wilbert; Zafar, Basit
<x xml:space="preserve">Abstract</x> We compare the inflation expectations reported by consumers in a survey with their behavior in a financially incentivized investment experiment. The survey is found to be informative in the sense that the beliefs reported by the respondents are correlated with their choices in the experiment. More importantly, we find evidence that most respondents act on their inflation expectations showing patterns consistent with economic theory. Respondents whose behavior cannot be rationalized tend to have lower education and lower numeracy and financial literacy. These findings help confirm the relevance of inflation expectations surveys and provide support to the microfoundations of modern macroeconomic models.